A Novel Cysteine-Sparing NOTCH3 Mutation in a Chinese Family with CADASIL - Ge, Wei (Public Library of Science, 2014)
Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is an adult onset cerebral small vessel disorder caused by the mutations of the neurogenic locus notch homolog protein 3 (NOTCH3) gene. The extracellular part of NOTCH3 is composed of 34 epidermal growth factor-like (EGF-like) repeat domains. Each EGF-like domain is rich of cysteine and glycine to produce three loops that are essential for high-affinity binding to its ligand. Nearly all reported CADASIL-associated mutations result in gain or loss of a cysteine residue within the EGF-like domains. Only a few cysteine-sparing NOTCH3 mutations have been documented in the patients with CADASIL to date. Here, we reported a Chinese CADASIL family with a cysteine-sparing NOTCH3 mutation. In this family, affected patients had dizziness, memory loss, gait instability, or hemiplegia. Brain magnetic resonance imaging (MRI) showed diffuse leukoencephalopathy with confluent signal abnormalities in the periventricular white matter, basal ganglia, and centrum semiovale bilaterally. By screening the entire coding region of NOTCH3, a novel missense mutation p.G149V (c.446G>T) was found. This mutation was not detected in 400 normal controls. Considering the critical position of glycine within the C-loop of EGF-like domain and its high conservation through evolution, p.G149V mutation could be a potential pathogenic cause for CADASIL.